2002
DOI: 10.1590/s1516-89132002000200007
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic changes in the kidney tissue of Prochilodus lineatus Valenciennes, 1836 (Characiformes, Prochilodontidae) induced by sublethal concentration of Trichlorfon exposure

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 8 publications
10
7
0
Order By: Relevance
“…Exposure to metals frequently causes alterations in the tubules and glomerulus, such as was described by Thophon et al (2003) for the perch (Lates calcarifer) exposed to cadmium; Handy and Penrice (1993) found swollen Bowmańs capsule cells and melanomacrophages in the kidney of trout (Salmo trutta) and tilapia (Oreochromis mossambicus) exposed to mercuric chloride. Similar alterations were found in fishes exposed to organic contaminants (Veiga et al 2002) and mixed environmental contaminants (Schwaiger et al 1997;Pacheco and Santos 2002). These reports suggest that the histopathological changes in the kidney could not be considered specific to the stressors.…”
Section: Resultssupporting
confidence: 53%
“…Exposure to metals frequently causes alterations in the tubules and glomerulus, such as was described by Thophon et al (2003) for the perch (Lates calcarifer) exposed to cadmium; Handy and Penrice (1993) found swollen Bowmańs capsule cells and melanomacrophages in the kidney of trout (Salmo trutta) and tilapia (Oreochromis mossambicus) exposed to mercuric chloride. Similar alterations were found in fishes exposed to organic contaminants (Veiga et al 2002) and mixed environmental contaminants (Schwaiger et al 1997;Pacheco and Santos 2002). These reports suggest that the histopathological changes in the kidney could not be considered specific to the stressors.…”
Section: Resultssupporting
confidence: 53%
“…In the present study, exposure of the common carp larvae to contaminated water showed degeneration in some epithelial cells of the renal tubules in addition to hypertrophy in epithelial cells of some other renal tubules were detected. Similar alterations were found by Veiga et al (2002) on the kidneys of other teleost fishes. However, short period of exposure may have no effect, because this phenomenon usually starts from 2 to 4 weeks after exposure to stressor and could even take 2 months to be completed (Gernhofer et al, 2001).…”
Section: Discussionsupporting
confidence: 83%
“…In more severe cases, the degenerative process leads to tissue necrosis (28). The present results are in agreement with those observed in C. carpio exposed to sewage (29), P. lineatus exposed trichlorfon (30) and L. calcarifer exposed to cadmium (27). Velmurugan, et al reported, histological changes in kidney of C. mrigala, exibiting necrosis of tubular epithelium, hypertrophied epithelial cells of renal tubules, expansion of space inside the Bowman's capsules exposed to fenvalerate (31).…”
Section: Discationsupporting
confidence: 92%